The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/raon-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Can dynamic imaging, using 18F-FDG PET/CT and CT perfusion differentiate between benign and malignant pulmonary nodules?

Abstract: Background The aim of the study was to derive and compare metabolic parameters relating to benign and malignant pulmonary nodules using dynamic 2-deoxy-2-[fluorine-18]fluoro-D-glucose (18F-FDG) PET/CT, and nodule perfusion parameters derived through perfusion computed tomography (CT). Patients and methods Twenty patients with 21 pulmonary nodules incidentally detected on CT underwent a dynamic 18F-FDG PET/CT and a perfusion C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Some of these preliminary studies did not show significant differences in the contrast between malignant and benign lesions. However, Ki, a marker of FDG metabolism, seems to be more suitable for predicting tumor cellular function and aggressiveness than SUV, a static FDG uptake marker in lung and breast cancer [97][98][99][100][101][102][103][104][105]. As many PET centers have had the chance to apply their up-to-date technology for parametric FDG analysis, these preliminary results will be confirmed in many oncology areas.…”
Section: Use Of Temporal Changementioning
confidence: 86%
“…Some of these preliminary studies did not show significant differences in the contrast between malignant and benign lesions. However, Ki, a marker of FDG metabolism, seems to be more suitable for predicting tumor cellular function and aggressiveness than SUV, a static FDG uptake marker in lung and breast cancer [97][98][99][100][101][102][103][104][105]. As many PET centers have had the chance to apply their up-to-date technology for parametric FDG analysis, these preliminary results will be confirmed in many oncology areas.…”
Section: Use Of Temporal Changementioning
confidence: 86%
“…Huang et al [16] concluded that in a small group of patients (N = 34), K i can better identify benign and malignant solitary pulmonary nodules (0.004 vs 0.023 ml/g/min, P = 0.0034) in areas (Taiwan) with a high prevalence of granulomatous disease. Aleksander et al [17] revealed that the lung malignancy group has higher K i values than the benign group (0.0230 ± 0.0155 vs.…”
Section: Discussionmentioning
confidence: 99%
“…CTPI can be used to evaluate the perfusion and vascularity of lesions in the lung and many other organs. [21][22][23][24][25][26][27][28] Wang et al 21 reported that parameters of CTPI (including BF, BV and PS but not MTT) of SPNs were significantly correlated with SPNs' microvessel density (MVD) and luminal vascular parameters such as luminal vascular number (LVN), luminal vascular area (LVA), and luminal vascular perimeter (LVP). Huang et al 22 analyzed the CT perfusion parameters (BF, BV, MTT, and PS) and the microvessel parameters (MVD, LVN, LVA, and LVP) in the non-small cell lung cancer (NSCLC) patients with and without lymph node metastasis.…”
Section: Ctpi In Evaluating Spnsmentioning
confidence: 99%